Hepatocystic fistula treated by cysticjejunal diversion - Palma, Eduardo; Fernández, Eliexer; Danza, Rómulo (Cirugía del Uruguay, 2020)
1) Areport is carried out of a case of suppurative calcified giant hepatic-hidatid cyst, with marked aero -anaerobian infection and very poor- general condition, treated by plain evacuation, extenal drainge and antibiogicogerapy, without drainage of the main biliary duct and with excellent course. 2) The chronic external hepatic –cystic fistula was treated by means of a Y shaped jejunal cystic anastomosis at the 4th jejunal loop, with gratifying results.